Evaluasi Pengalaman Ulangan Harian menggunakan Quizizz dengan Model CIPP (Studi Kasus: SDN Madiopuro Jombang) - Novia Tri Rahmawati; Intan Sartika Eris Maghfiroh; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Elementary school is an education category that must be considered for its quality, because learning at the elementary level is the initial foundation before students move on to the next level. However, due to the COVID-19 pandemic, the learning process is not optimal. The learning process before the pandemic was carried out face-to-face, but learning is currently forced to switch online (on a network). The impact of the application of online learning makes students feel bored, their enthusiasm for learning decreases, and even students' grades are also decreasing. In response to this, the principal of SDN Madiopuro implemented the use of Quizizz which was expected to increase students' enthusiasm for learning. So far, the application has only been carried out in one class, because valid data is needed regarding information on the Quizizz implementation that has been implemented. The purpose of this study was to find out how the experiences of students and teachers in using Quizizz. In addition, this study will analyze the value before and after using Quizizz. To find out the comparison of data, data is needed for classes that do not use Quizizz. Therefore, this study is a comparative study comparing classes that use and do not use Quizizz. The results of this study indicate that the class that uses Quizizz gets a better average score, and all students in the class agree that Quizizz is easy to use and fun.